Comparative Effects of Volutrauma and Atelectrauma on Lung Inflammation in Experimental Acute Respiratory Distress Syndrome. Issue 9 (September 2016) - Güldner, Andreas; Braune, Anja; Ball, Lorenzo; Silva, Pedro L.; Samary, Cynthia; Insorsi, Angelo; Huhle, Robert; Rentzsch, Ines; Becker, Claudia; Oehme, Liane; Andreeff, Michael; Vidal Melo, Marcos F.; et al.
Abstract : Objective: Volutrauma and atelectrauma promote ventilator-induced lung injury, but their relative contribution to inflammation in ventilator-induced lung injury is not well established. The aim of this study was to determine the impact of volutrauma and atelectrauma on the distribution of lung inflammation in experimental acute respiratory distress syndrome. Design: Laboratory investigation. Setting: University-hospital research facility. Subjects: Ten pigs (five per group; 34.7–49.9 kg) Interventions: Animals were anesthetized and intubated, and saline lung lavage was performed. Lungs were separated with a double-lumen tube. Following lung recruitment and decremental positive end-expiratory pressure trial, animals were randomly assigned to 4 hours of ventilation of the left (ventilator-induced lung injury) lung with tidal volume of approximately 3 mL/kg and 1) high positive end-expiratory pressure set above the level where dynamic compliance increased more than 5% during positive end-expiratory pressure trial (volutrauma); or 2) low positive end-expiratory pressure to achieve driving pressure comparable with volutrauma (atelectrauma). The right (control) lung was kept on continuous positive airway pressure of 20 cm H2 O, and CO2 was partially removed extracorporeally. Measurements and Main Results: Regional lung aeration, specific [ 18 F]fluorodeoxyglucose uptake rate, and perfusion were assessed using computed and positron emission tomography. Volutrauma yielded higher [ 18 F]fluorodeoxyglucose uptake rate in the ventilated lung compared with atelectrauma (median [interquartile range], 0.017 [0.014–0.025] vs 0.013 min –1 [0.010–0.014 min –1 ]; p < 0.01), mainly in central lung regions. Volutrauma yielded higher [ 18 F]fluorodeoxyglucose uptake rate in ventilator-induced lung injury versus control lung (0.017 [0.014–0.025] vs 0.011 min –1 [0.010–0.016 min –1 ]; p < 0.05), whereas atelectrauma did not. Volutrauma decreased blood fraction at similar perfusion and increased normally as well as hyperaerated lung compartments and tidal hyperaeration. Atelectrauma yielded higher poorly and nonaerated lung compartments, and tidal recruitment. Driving pressure increased in atelectrauma. Conclusions: In this model of acute respiratory distress syndrome, volutrauma promoted higher lung inflammation than atelectrauma at comparable low tidal volume and lower driving pressure, suggesting that static stress and strain are major determinants of ventilator-induced lung injury. Abstract : Supplemental Digital Content is available in the text.